In vivo knockdown of Piccolino disrupts presynaptic ribbon morphology in mouse photoreceptor synapses - Regus-Leidig, Hanna (Frontiers Media S.A., 2014)
Piccolo is the largest known cytomatrix protein at active zones of chemical synapses. A growing number of studies on conventional chemical synapses assign Piccolo a role in the recruitment and integration of molecules relevant for both endo- and exocytosis of synaptic vesicles, the dynamic assembly of presynaptic F-actin, as well as the proteostasis of presynaptic proteins, yet a direct function in the structural organization of the active zone has not been uncovered in part due to the expression of multiple alternatively spliced isoforms. We recently identified Piccolino, a Piccolo splice variant specifically expressed in sensory ribbon synapses of the eye and ear. Here we down regulated Piccolino in vivo via an adeno-associated virus-based RNA interference approach and explored the impact on the presynaptic structure of mouse photoreceptor ribbon synapses. Detailed immunocytochemical light and electron microscopical analysis of Piccolino knockdown in photoreceptors revealed a hitherto undescribed photoreceptor ribbon synaptic phenotype with striking morphological changes of synaptic ribbon ultrastructure.